KEMANDIRIAN GERAKAN CINTA SONIK (SAMPAH ORGANIK) MENGELOLA SAMPAH DARI SUMBER RUMAH TANGGA DESA LENGKONG KECAMATAN BOJONGSOANG KABUPATEN BANDUNG - Kurniawati, Ratna Dian; Fauziah, Diah Adni; Stellata, Alyxia Gita; Munawaroh, Madinatul; Oktafiani2, Hani; Setiawati, Rita; Nurhaliza, Farah; Hidayana, Haiqal Akbar; Nugraha, Mochamad Faisal (Universitas Mataram, 2024)
Efforts to process waste at the source are a must considering that the Sarimukti Landfill (TPA) only accepts 50% of waste. These efforts include reducing waste with Reduce, Reuse and Recylce method and processing waste independently through simple composting. RT 01/013 area of Lengkong Village, Bojongsoang District is a densely populated settlement that has had a Reduce, Reuse, Recycle Waste Management Site (TPS 3R) for the Bagja Self-Help Group (KSM) since 2021. This TPS 3R can only accommodate the waste of 3 RW out of 17 RW in Lengkong Village. This means that the existence of TPS 3R KSM Bagja hasn’t been able to accommodate the volume of waste. This community service aims to increase community knowledge, especially RT 01/013 Lengkong Village about processing household organic waste. The community service method with the theme